Saudi Arabian Men's Fashion Transformation: Tsaub, Ghutra and Bisht Towards Vision 2030 - Sultan Alam Koto; Febri Priyoyudanto (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
implementation of the Saudi Vision 2030 strategic agenda has triggered significant socio-cultural transformations, driving a reconfiguration of national identity that is manifested in the evolution of men's fashion aesthetics. This study addresses a lacuna in existing literature, which tends to position traditional clothing as static cultural artifacts, with the objective of comprehensively analyzing the transformation of design, function, and symbolic meaning of three primary garment elements: thobe, Ghutra, and Bisht. Employing a qualitative approach through a systematic literature review of historical sources, policy documents, and contemporary studies, this research maps the evolution of these garments from the pre-modern era to the present. The findings indicate that these three elements have undergone a fundamental paradigm shift: the thobe has transformed from a utilitarian desert garment into a symbol of urban professionalism; the Ghutra has evolved from a physical protector into an attribute of hyper-nationalism and youth stylistic expression; while the Bisht has experienced democratization from a symbol of elite exclusivity to an inclusive instrument of cultural diplomacy (soft power). This study concludes that modernization in Saudi Arabia does not erode tradition but rather effects a cultural recontextualization, wherein fashion functions as a dynamic medium in the negotiation of a national identity that is adaptive to global demands.